Effect of nutrient management strategies on productivity in rice-pigeon pea intercropping under drought prone rainfed ecology of Eastern India - Verma, BC; Mandal, NP; Roy, S; Prasad, SM; Banerjee, A (ORYZA-An International Journal of Rice, 2022)
An experiment was undertaken to compare the productivity of rice- sole with rice-pigeon pea intercropping under different nutrient management (inorganic, organic and integrated nutrient management) strategies in drought prone rainfed (upland) ecology. The experimental data showed that, rice equivalent yield (REY) (2.83 and 3.22 t ha-1 under rice sole and rice -pigeon pea respectively) and yield attributing characters (grain panicle-1 (73) and test weight (24.3g) were higher under inorganic nutrient management followed by the integrated nutrient management (T4) (2.25 t ha-1, 2.64 t ha-1, 64 and 22.7 g respectively). The yield gap between the inorganic and integrated nutrient management decreased over the three years, because, in the first year integrated nutrient management could not produce enough yield and difference was more which became narrow as this treatment produced comparatively more yield afterward. REY was more in rice-pigeon-pea system (varied from 1.13 to 3.22 t ha-1) over the rice-sole (1.01 to 2.83 t ha-1) across the nutrient management strategies. Thus it is evident that, rice- pigeon pea intercropping under integrated nutrient management in upland condition would be better choice in rainfed drought prone area to enhance farm income as well as system productivity.